An uncommon cause of acute hypercapnic respiratory failure managed with endoscopic ultrasound - Vishal Raj; Aman Ahuja; Monika Gupta; Dhruva Chaudhry; Pawan Kumar Singh (Lung India)
Mediastinal cysts can occasionally cause severe respiratory symptoms. A 60-year-old female smoker presented with acute hypercapnic respiratory failure. Imaging revealed a posterior mediastinal cyst compressing the trachea. Bronchoscopic ultrasound-guided fine needle aspiration (EUS-B FNA) provided both diagnostic clarity and symptomatic relief. This case underscores the importance of considering mediastinal cysts in differential diagnoses of acute respiratory distress and demonstrates the efficacy of EUS-B FNA for both diagnosis and immediate therapeutic intervention.